Imaging of Corneal Neovascularization: Optical Coherence Tomography Angiography and Fluorescence Angiography - Brunner, Matthias; Romano, Vito; Steger, Bernhard; Vinciguerra, Riccardo; Lawman, Samuel; Williams, Bryan; Hicks, Nicholas; Czanner, Gabriela; Zheng, Yalin; Willoughby, Colin E.; Kaye, Stephen B. (Investigative ophthalmology & visual science, 2018)
The purpose of this study was to compare optical coherence tomography angiography (OCTA) and indocyanine green angiography (ICGA) for the assessment of corneal neovascularization (CoNV). Patients with CoNV extending at least 3 mm into the cornea were included. All patients underwent corneal imaging at the same visit. Images were recorded using the AngioVue OCTA system (Optovue, Inc.) with the long corneal adaptor module (CAM-L). ICGA images were recorded with fluorescent filters using the Heidelberg system (HRA2 Scanning Laser Ophthalmoscope; Heidelberg Engineering). Images were graded for quality by two independent observers. Vessel parameters: area, number, diameter, branch and end points, and tortuosity, were compared between devices. Bland-Altman plots were used to assess differences between parameters. Fifteen patients with CoNV predominantly associated with microbial keratitis were included. Mean subjective image quality score was better for ICGA (3.3 ± 0.9) than for OCTA (2.1 ± 1.2, P = 0.002), with almost perfect interobserver agreement for ICGA images (κ = 0.83) and substantial agreement for OCTA images (κ = 0.69). Agreement of grading of all investigated vessel parameters between ICGA and OCT images was slight to moderate, with significant differences found for vessel diameter (-8.98 μm, P = 0.01, 95% limits of agreement [LOA]: -15.89 to -2.07), number of branch (25.93, P = 0.09, 95% LOA: -4.31 to 56.17), and terminal points (49, P = 0.05, 95% LOA: 0.78 to 97.22). Compared with ICGA, current OCTA systems are less precise in capturing small vessels in CoNV complexes, and validation studies are needed for OCTA segmentation software. OCTA, however, complements ICGA by providing evidence of red blood cell flow, which together with depth information, may be helpful when planning treatment of CoNV.